Liquidity and Activity Analysis on Profitability at PT Eastparc Hotel TBK 2019-2021 (Pandemic Conditions) - Rhea Mandasari; Fabiola Kalalo; Vanessa Jaklin; Islamiati Wulandari; Dyah Cahyasari (Al Makki Publisher, 2023)
The COVID-19 pandemic has had a continuous impact on various sectors, including the economic and tourism sectors, which has caused a decline in production, consumption, and operations in all aspects including maintaining the company's existence and safe and stable profitability. This study aims to analyze profitability using methods from liquidity ratios and activity ratios based on PT Eastparc Hotel Tbk's financial statements from 2019-2021. Data collection method through theory from several literature reviews with time series data collection techniques. The data analysis method used is descriptive quantitative using financial ratio analysis tools, with a research period of the last 3 years (2019 – 2021). The results of the analysis of CR's liquidity ratio for 3 years during the pandemic show that the company PT Eastparc Hotel Tbk has not been able to pay debts that must be immediately met with current assets. QR and CAR show that the company's condition is not good in 2021 This condition means that the company still needs time to sell some of its other current assets to pay its obligations. The results of the Activity ratio show that the company's performance is not good and able to maximize the capacity of its fixed assets. Meanwhile, inventory turnover shows good company conditions in maximizing inventory so as not to accumulate in warehouses in excess quantities (productive) increasing profitability. Meanwhile, the working capital turnover ratio in 2019 was not good, but there were improvements in the last two periods, namely 2020 and 2021. The results of the financial ratio analysis show that PT Eastparc Tbk.'s financial performance during the 3 periods of the pandemic was quite good, after improving its ability to pay short-term debt through the sale of securities, collecting even though inventory turnover was slow and had a relationship in line with the decline in profitability generated by the company.